Desenvolvimento de uma editora científica sobre uma rede blockchain permissionada - DEFRÉMONT, André (2019)
This paper deals with the development (specification, implementation and evaluation) of a web application that should act as a decentralized scientific publisher, using Blockchain technology for intelligent contracts and hypermedia storage. The security of stored data is a concern in many software, which has contributed to a better understanding of distributed processes and softwares. Data storage systems that use Blockchain technology emerge as an alternative to ensure information integrity through decentralized storage, auditing, and transparency. Decentralized applications have proven to be more efficient, safer and cheaper. This discussion extends to the scientific community in the scenario of publication and revision of scientific articles. Researchers use publishing tools to publicize their work and want to gain some control over profit, copyright, and content review. With Blockchain, solutions such as Hyperledger and IPFS (Interplanetary File System) enabled the management of this content through the logics of a traditional publisher in an autonomous, decentralized and secure way. This work is the proof of concept of a broader research carried out in the GERCOM laboratory at UFPA, the DASP (Decentralized Autonomous Software Publisher), which aims to broaden the management of the editorial process, removing intermediates, in order to optimize the process between the entities involved (community). The system developed in this work allows authors to register and allows them to submit articles to the IPFS network to have their hash stored in Hyperledger Fabric where it will be available to be evaluated by registered reviewers on the network through the rules of the smart contract. The implementation of the code was done in the Javascript language (NodeJS), with the help of the Dependencies: angular4, react, go-ipfs, hyperledger-composer, the database is IPFS for hypermedia and Hyperledger Fabric for transactions, participants and assets . The implemented system was validated through the technical evaluation of the elaborated diagrams and by evaluation questionnaires with real users, in a scenario that contemplates the sending, revision and publication of a scientific article, in an intranet.